2009
DOI: 10.1116/1.3039683
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nanogap electrodes by field-emission-induced electromigration

Abstract: Controlling the tunnel resistance of suspended Ni nanogaps using field-emission-induced electromigration J. Vac. Sci. Technol. B 33, 02B107 (2015); 10.1116/1.4904731Fabrication of planar-type Ni/vacuum/Ni tunnel junctions based on ferromagnetic nanogaps using field-emissioninduced electromigrationThe authors report a simple and easy technique for the fabrication of nanogaps with separations of less than 10 nm. This technique is based on electromigration induced by field emission current. Here, the authors inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Recently, Araidai et al have found using first-principles calculations based on the densityfunctional theory (DFT) that surface atom under field emission (FE) evaporates with lower fields than the typical strength of field evaporation without FE. Then, FE-assisted surface atoms evaporate in the same direction as the electron flow [13], which is in good agreement with the direction of moving atoms controlled by the "activation" [11,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Recently, Araidai et al have found using first-principles calculations based on the densityfunctional theory (DFT) that surface atom under field emission (FE) evaporates with lower fields than the typical strength of field evaporation without FE. Then, FE-assisted surface atoms evaporate in the same direction as the electron flow [13], which is in good agreement with the direction of moving atoms controlled by the "activation" [11,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 78%
“…In the activation scheme, when the field emission current flows from drain to source electrode, Ni atoms at the tip of the source electrode are activated and then are migrated from source to drain electrode [11,12,[14][15][16]. Recently, Araidai et al have found using first-principles calculations based on the densityfunctional theory (DFT) that surface atom under field emission (FE) evaporates with lower fields than the typical strength of field evaporation without FE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has previously achieved the fabrication of SETs by using electromigration that was induced by field emission currents flowing through the nanogaps, referred to as "activation." [10][11][12][13][14] In addition, we found that the number of islands formed during the formation of the SETs can be controlled by the magnitude of the preset current used in the activation procedure. 13,14 Furthermore, we have reported the formation of a single-island SET.…”
Section: Introductionmentioning
confidence: 88%
“…The sequence of steps for performing activation on the nanogaps has been described in detail in our previous studies. [10][11][12][13][14] As shown in Fig. 1(b), following the activation, the characteristics of the SETs were investigated with dc measurements both at 18 K and at room temperature.…”
Section: -3mentioning
confidence: 99%